2021
DOI: 10.3389/ffgc.2021.674138
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Lessons From the Southeast United States Woody Pellet Supply Chain Response to the COVID-19 Pandemic†

Abstract: The Coronavirus Disease 2019 (COVID-19) instigated a pandemic that impacted economies, employment, and shipping worldwide. This paper reviews how one international supply chain performed and identifies lessons that may be helpful to improve future resilience. Economic and employment data through November 2020 are used to review the effects of COVID-19 on operations of the bioenergy supply chain in the southeastern United States (SE United States) that utilizes wood fiber to fabricate pellets. Conditions associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…The pandemic exposed limitations (short run) and opportunities (long run) in dealing with energy supply, in general, and the role of biomass, in particular. The food supply chain review identified small farmers as a group particularly affected by the pandemic, and study experts emphasized a need to avoid food protection policies to prevent an increase in food prices, consistent with other publications [57,58]. Others highlighted the vulnerability of SMEs in general [3].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The pandemic exposed limitations (short run) and opportunities (long run) in dealing with energy supply, in general, and the role of biomass, in particular. The food supply chain review identified small farmers as a group particularly affected by the pandemic, and study experts emphasized a need to avoid food protection policies to prevent an increase in food prices, consistent with other publications [57,58]. Others highlighted the vulnerability of SMEs in general [3].…”
Section: Discussionsupporting
confidence: 61%
“…Experts reported different resilience of BSChs to the economic disturbances due to the pandemic during the first six months (by September 2020), which is supported by research (e.g., [57][58][59]) published after the survey had been implemented. For instance, health and food safety measures resulted in increased interest in automation and robotics in the food and beverage industry as compensation for the limited availability of workers [4,60].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Canada's forest sector was affected by the drastic changes in demand for forest products over the course of the pandemic, a trend also observed in the United States [6]. Although the Canadian forest sector is well acquainted with market shocks and had taken steps to mitigate anticipated risks [7,8], it was unclear how exactly the sector would be affected at the onset of the COVID-19 pandemic and how these impacts would spill over Energies 2022, 15, 3179 2 of 18 into related industries.…”
Section: Introductionmentioning
confidence: 94%